Greening the Region: Metropolitan Governance and Biodiversity Protection in Montreal and Toronto - Medicoff, Joshua; Béland, Daniel (Canadian Planning and Policy / Aménagement et politique au Canada, 2024)
Recognizing that biodiversity loss and climate change are twin crises, urban regions across the world are seeking to implement biodiversity strategies through specific forms of urban governance embedded in existing institutional legacies. To understand the effects of metropolitan institutions on the governance of urban biodiversity, we examine the institutional and regional structures of Canada’s two most populous metropolitan regions, Greater Montreal and Greater Toronto. This article compares the distinct policy consequences of the institutional set-up of Greater Montreal and Greater Toronto. This includes understanding how a second tier of government in Montreal (the Communauté métropolitaine de Montréal), which sets biodiversity protection and conservation targets in the Montreal region, contrasts with the Toronto region, whose larger region is more directly governed by the Province of Ontario. Drawing on both the work of Elinor Ostrom on metropolitan governance and interviews with urban actors in both urban areas under consideration, we show how fragmented institutional arrangements are dominated by provincial management (as the case is for the Toronto region), and lead to worse outcomes for biodiversity.